2011
DOI: 10.1002/lary.22388
|View full text |Cite
|
Sign up to set email alerts
|

Video laryngoscopy‐assisted secondary tracheoesophageal puncture placement for the patient with severely limited neck extension

Abstract: Secondary tracheoesophageal puncture (TEP) placement in patients with severe limitations in neck extension is challenging. Visualization of the hypopharynx with traditional rigid endoscopy may not be possible. We report using the C-MAC (Karl Storz, Tuttlingen, Germany) video laryngoscope to successfully place a secondary TEP in patient with severe radiation fibrosis at a tertiary referral center. A 59-year-old male with severe radiation fibrosis of the neck underwent total laryngectomy for a nonfunctioning lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Should the technique prove suitable for application in humans, it will require the ability to perform TNE. Although other methods of direct visualization (eg, video laryngoscopy) have been applied during secondary TEP, such techniques may be difficult to use under local anesthesia in the office, and cannot provide the same detailed view, particularly if there is difficult anatomy or trismus to negotiate . The need for TNE may well be offset by advantages from using this technique, and TNE is becoming increasingly widely available in head and neck surgery units, so the technique may simply provide an extension of its application.…”
Section: Discussionmentioning
confidence: 99%
“…Should the technique prove suitable for application in humans, it will require the ability to perform TNE. Although other methods of direct visualization (eg, video laryngoscopy) have been applied during secondary TEP, such techniques may be difficult to use under local anesthesia in the office, and cannot provide the same detailed view, particularly if there is difficult anatomy or trismus to negotiate . The need for TNE may well be offset by advantages from using this technique, and TNE is becoming increasingly widely available in head and neck surgery units, so the technique may simply provide an extension of its application.…”
Section: Discussionmentioning
confidence: 99%
“…However, under certain conditions secondary TEP can be necessary. Indications for secondary TEP include failure of non–prosthesis‐associated speech devices, deficient primary TEP, or lack of primary TEP during laryngectomy . Being confronted with the need for secondary TEP, the procedure can be challenging due to insufficient head reclination or mouth opening caused by degenerative changes of the cervical spine, trismus, pharyngeal reconstruction (e.g., microvascular free tissue transfer), or scar tissue formation in postirradiated patients.…”
Section: Discussionmentioning
confidence: 99%
“…Indications for secondary TEP include failure of non-prosthesis-associated speech devices, deficient primary TEP, or lack of primary TEP during laryngectomy. 10 Being confronted with the need for secondary TEP, the procedure can be challenging due to insufficient head reclination or mouth opening caused by degenerative changes of the cervical spine, trismus, pharyngeal reconstruction (e.g., microvascular free tissue transfer), or scar tissue formation in postirradiated patients. Under these conditions, the safe and well-established method of inserting the voice prosthesis by using rigid scopes as protection of the posterior upper esophageal wall can be challenging and sometimes not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Crozier et al [13] have reported on visualization of the TEP through videolaryngoscopy. This may not be feasible, however, for patients with long necks, severe contracture, or hypopharyngeal stenosis and does not protect the posterior esophageal wall from injury.…”
Section: Discussionmentioning
confidence: 99%